Beyond Scapegoating: Greenhouse Effect Mechanisms and Hydrometeorological Anomalies as Primary Drivers of Disasters-Challenging the Misattribution to Oil Palm Plantations - Loso Judijanto (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to critically examine public attributions that tend to simplify the causes of flash floods and hydrometeorological disasters in Indonesia by linking them solely to oil palm plantations. The study employed a qualitative literature review of scientific articles, research reports, and relevant documents from 2020–2025. Data were analyzed using content analysis and narrative synthesis techniques to identify the relationship between climate change, environmental factors, and social dynamics in flooding events. The study results indicate that flash floods occur widely, including in areas without oil palm plantations, such as Java and coastal urban areas. The main factors influencing flooding include extreme rainfall, urbanization, land subsidence, spatial planning damage, and anthropogenic climate change. The literature also indicates that not all oil palm plantations are the primary cause of deforestation, as some are developed on degraded land. This study emphasizes the importance of a science-based approach and systems thinking in understanding disaster risk, enabling more objective and sustainable public communication and environmental policy development.